2013
DOI: 10.1242/jcs.120162
|View full text |Cite
|
Sign up to set email alerts
|

Raft endocytosis of autocrine motility factor regulates mitochondrial dynamics via rac1 signaling and the gp78 ubiquitin ligase

Abstract: SummaryGp78 is a cell surface receptor that also functions as an E3 ubiquitin ligase in the endoplasmic reticulum (ER)-associated degradation (ERAD) pathway. The Gp78 ligand, the glycolytic enzyme phosphoglucose isomerase (PGI; also called autocrine motility factor, AMF), functions as a cytokine upon secretion by tumor cells. AMF is internalized through a PI3K-and dynamin-dependent raft endocytic pathway to the smooth ER; however, the relationship between AMF and Gp78 ubiquitin ligase activity remains unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Stable HT-1080 clones expressing control shCtl and Gp78-targeted shGp78 shRNAs (corresponding to sh6 Gp78 shRNA in Shankar et al, 2013) in doxycyclin-inducible pTRIPZ plasmid were maintained in medium containing 2 mg/ml puromycin and 1 mg/ml doxycyclin to induce Gp78 knockdown. For AMF treatment, cells were serum starved overnight and incubated with fresh medium containing 24 ”g/ml AMF.…”
Section: Cell Culture Constructs and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable HT-1080 clones expressing control shCtl and Gp78-targeted shGp78 shRNAs (corresponding to sh6 Gp78 shRNA in Shankar et al, 2013) in doxycyclin-inducible pTRIPZ plasmid were maintained in medium containing 2 mg/ml puromycin and 1 mg/ml doxycyclin to induce Gp78 knockdown. For AMF treatment, cells were serum starved overnight and incubated with fresh medium containing 24 ”g/ml AMF.…”
Section: Cell Culture Constructs and Treatmentsmentioning
confidence: 99%
“…The ER is associated with mitochondrial fission sites (Friedman et al, 2011) and Gp78 ubiquitin ligase activity targets the mitochondrial fusion proteins, mitofusin 1 (Mfn1) and Mfn2, for degradation inducing mitochondrial fission and, upon mitochondrial depolarization, mitophagy . Dynamin-and Rac1-PI3K-dependent raft internalization of AMF to the Gp78-positive ER prevents Gp78 degradation of the mitofusins and reverses Gp78-dependent mitochondrial fission (Kojic et al, 2007;Le et al, 2002;Shankar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…; Shankar et al . ), and is reported to protect against ER stress and apoptosis by regulation of ER calcium release (Fu et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…neuroleukin; autocrine motility factor) is a pleiotropic protein performing different functions inside the cell and in the extracellular space. In the cytoplasm, GPI catalyzes the second step in glycolysis, regulates gp78-dependent mitochondrial fission and mitophagy Shankar et al 2013), and is reported to protect against ER stress and apoptosis by regulation of ER calcium release (Fu et al 2011). Outside the cell, GPI acts as a neurotropic factor for spinal and sensory neurons, contributing to maintenance of neuronal integrity (Haga et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that some bacterial toxins of the Clostridium family can hijack the IL2-R pathway for cell intoxication (41). The AMF is endocytosed by a pathway that is regulated in a similar manner except for the sensitivity to RhoA (42). It is not known whether IFNAR and IFNGR can take the IL2-R endocytic route.…”
Section: Clathrin-independent Endocytosismentioning
confidence: 99%